Pendidikan Akhlak/karakter Berbasis Al-Qur'an dan Hadist - asha, ashari nurwahidaturrahim; Hasanah, Diniatul; Edy (Edusifa: Jurnal Pendidikan Islam, 2023)
This country is looking for and reaching an agreement on a solution that would improve the country while also meeting the criteria of basic education. Islam certainly greatly ennobles humans, the process of education and human development in the concept of character education is enriched by an ideal example, namely the Nabawi madrasah, (the Prophet's educational model). The Nabawi Madrasah succeeded in changing human character from jahiliyah to Islamiyah so that it turned 180 degrees. Despite social illusions about education, there is hope for the emergence of a character education age based on the Quran and Hadith. Love for God and everything created, integrity, self-reliance, accountability, dependability, diplomacy, politeness and respect, compassion and generosity, diligence and self-assurance, leadership and justice, humility, tolerance, peace, and unity are the nine pillars of this movement.